Pengembangan Media Pembelajaran Berbasis Video Tutorial Mata Pelajaran Dasar Desain Grafis Pada Kelas X Multimedia di SMK Negeri 1 Sakra - Gebi Juan Giana; Samsul lutfi; Jamaluddin Jamaluddin (Jurnal Pendidikan Informatika (EDUMATIC), 2019)
This study aims to development of tutorial video-based learning media on subject of basic graphic design for student of tenth grade of Multimedia at Vocational High School I Sakra,  The level of video-based learning media feasibility tutorial on subject of basic graphic design for student of tenth grade of Multimedia at Vocational High School I Sakra, and Students' response to video-based learning tutorial on subject of basic graphic design for student of tenth grade of Multimedia at Vocational High School I Sakra. The study method used was R D (Research and Development) with the development model of ADDIE. The instrument of data collection used a questionnaire with a Likert scale. The data used was qualitative data and quantitative data. Data collection used was observation, interview, and questionnaire. The analysis technique used was through the feasibility test of media expert and material expert. The result showed that the video tutorial-based learning media developed were feasible to use with the result of the feasibility of media experts 70% with eligible criteria, while the material expert 78% with eligible criteria. Meanwhile, the product trial obtained a percentage score of 65%. Thus this video tutorial based learning media is worthy of being used as a learning medium for the student of the tenth grade of the multimedia major for Photoshop material on Basic Graphic Design subject.